Exchange-Rate Dark Matter - Evans, Martin (IMF Working Papers; Working Paper, 2012)
Dark matter accounts for 83 percent of the matter in the universe and plays a central role in cosmology modeling. This paper argues that an analogous form of dark matter plays a similarly important role in international macroeconomics. Exchange-rate dark matter is invisible, but its existence can be inferred from observations on real exchange rates and interest rates. I first show that dark matter is the dominant driver of short- and medium-term changes in real exchange rates for the G-7 countries; accounting for more than 90 percent of the variance at the five-year horizon. I then develop a model in which risk shocks account for dark matter's role as a driver of exchange-rate dynamics and other macro variables.